2012
DOI: 10.1017/s1368980012001292
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption among migrants in Switzerland

Abstract: Objective: To assess the relative risk of low daily fruit and vegetable consumption for six large migrant groups in Switzerland. Design: Cross-sectional health survey carried out 2007 (Swiss Health Survey) and 2010 (Swiss Migrant Health Survey) in Switzerland. Multinomial logistic regression models were used to estimate relative risk rates (RRR) of migrants relative to Swiss nationals. Setting: Data obtained from representative samples of Swiss and foreign nationals living in Switzerland. Subjects: A random sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
3
8
1
Order By: Relevance
“…This result is inconsistent with previous studies that obtained strong correlations between autonomous motivation and fruits and vegetable intake [16,51]. A reason for this inconsistency could be the cultural diversity found in our study population and the different aspects of food socialisation they represent (cooking and eating behaviours including different commensality practices) [52], which could influence the sources of the regulation when following a healthy diet [53,54].…”
Section: Discussioncontrasting
confidence: 99%
“…This result is inconsistent with previous studies that obtained strong correlations between autonomous motivation and fruits and vegetable intake [16,51]. A reason for this inconsistency could be the cultural diversity found in our study population and the different aspects of food socialisation they represent (cooking and eating behaviours including different commensality practices) [52], which could influence the sources of the regulation when following a healthy diet [53,54].…”
Section: Discussioncontrasting
confidence: 99%
“…These are all good sources of vitamin K. Similar results for the distribution of vegetable-derived vitamin K levels were found in 2013 study from the School of Health Professions, Zurich University of Applied Sciences. That study compared the fruit and vegetable consumption of migrants living in Switzerland, including Portuguese migrants, with their Swiss counterparts and showed that migrants from Portugal had a lower vegetable intake than the Swiss [35]. This result is in accordance with the present study, where Portuguese women in Switzerland are the group with the lowest vitamin K intake from vegetables, which indirectly shows the lower intake of vegetables in the diet in comparison with the control groups [13].…”
Section: Discussionsupporting
confidence: 91%
“…As shown in Table 1 , the ‘social and cultural environment’ cluster contained the highest number of factors influencing dietary behaviours. These factors include cultural identity and desire to maintain traditional food identity [ 9 , 30 34 ], religious beliefs and prescriptions [ 25 , 35 – 38 ], social networks [ 10 ], social bonding [ 36 ], level of acculturation and socialization processes [ 10 , 29 , 34 ], social norms/social role of food [ 38 ] and gender [ 28 , 39 , 40 ]. Another set of factors was grouped under the cluster ‘accessibility of food’.…”
Section: Resultsmentioning
confidence: 99%